On polyphyly of the former section Ochlopoa and the hybridogenic section Acroleucae (Poa, Poaceae): insights from molecular phylogenetic analyses. (3rd April 2019) - Nosov, Nikolai N.; Tikhomirov, Valery N.; Machs, Eduard M.; Rodionov, Alexander V.
Abstract : In this study, sequence data from the inert nuclear region ITS1‐5.8S rDNA‐ITS2 and the chloroplast region trnL–F, as well as a few morphological characters, are analysed to the relationships among known annual Poa (bluegrasses). It is shown that all taxa from the Poa annua aggregate distinguished by lemma characters and growth form have identical ITS and trnL–trnF sequences, all ITS sequences of this aggregate are the same as thethose of P. supina, and all trnL–trnF sequences are homologous with those of P. infirma . Furthermore, no differences were found between unusual morphotypes of P. supina with short spinules on their panicle branches and typical plants, but Siberian samples were found to have a slightly differentiated trnL–trnF region. These results suggest a hybrid origin of the Asian annual bluegrasses. Their maternal genome is close to that of P . sect. Homalopoa, but their ITS sequences are different. Some ITS sequences from annual Asian bluegrasses are resolved among representatives of P . sect. Stenopoa while for other (morphologically closely similar) species they fall in a clade with representatives of P . sect. Malacanthae . The latter group is distant from P . sect. Ochlopoa and is better treated as a separate section, viz P . sect. Acroleucae . The American annual bluegrasses are heterogeneous and also rather distant from P . sect. Ochlopoa . Poa chapmaniana, a species with cleistogamic flowers, is nested among the basal Subantarctic sections, far away from the taxa with which it has previously been considered related. It is indeed closer to P . sect. Ochlopoa than to other annual American bluegrasses. Thus, the studied annual species in fact belong to four independent evolutionary lines (or six including the separate genus Eremopoa and the Turkish Poa jubata ), one of which, Acroleucae, has gone through three reticulation events. As in previous studies, our analysis did not support the generic status of P . sect. Ochlopoa .